As mídias sociais e o terceiro setor: uma análise das organizações da área da saúde de São Borja - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Althoug the internet were a pretty discussed subject in Comunications área, when it were related to the third sector, the theme stops beeing a prominence. Therefore, in order to study a theme not so explored yet and provide new data and reflections about it, this research has as general objective map the presence of nonprofit organizations in social medias, specifically those wich works on health area in São Borja city. For that, it were used as object of study the following organizations: Grupo de Apoio aos Pacientes Oncológicos de São Borja (GAPO-SB), Liga Feminina de Combate ao Câncer de São Borja, Sociedade Beneficente Ivan Goulart (SBIG). To answer the proposed objective, this research makes use of a descriptive research of qualitative character, which has as methodology the use of bibliographic research, exploratory research, in-depth interview and documentary analysis. The obtained information will attend not only to self-interests, but also will contribute with the third sector and future researches, supplying data that until now were nonexistent in the municipality.
Keywords: Internet; Associações sem fins lucrativos; Mídia social; Áreas de serviço de saúde; São Borja (RS); Non-Profit Associations; CNPQ::CIENCIAS SOCIAIS APLICADAS